Physical activity and life satisfaction among individuals with spinal cord injury: Exploring loneliness as a possible mediator. (4th March 2022) - Santino, Nicholas; Larocca, Victoria; Hitzig, Sander L.; Guilcher, Sara J.T.; Craven, B. Catharine; Bassett-Gunter, Rebecca L.
Abstract : Context: There has been no known research investigating the association between leisure time physical activity (LTPA), loneliness, and life satisfaction among people with spinal cord injury or dysfunction (SCI/D). The relationship between these constructs is worthy of consideration given the positive health impacts of LTPA, the negative health impacts of loneliness, and heightened negative effects of loneliness on life satisfaction for individuals with SCI/D. Objectives: To examine the relationship between LTPA and loneliness, and examine loneliness as a possible mediator of the relationship between LTPA and life satisfaction among individuals with SCI/D. Design and Participants: Community dwelling individuals with SCI/D ( N  = 170) participated in a telephone-based survey as part of a larger project. Measures: LTPA (i.e. The Leisure Time Physical Activity Questionnaire-SCI, UCLA Loneliness Scale-3, and the Life Satisfaction Questionnaire-11 were administered to the participants. Results: Significant bivariate relationships were observed between LTPA and life satisfaction ( r  = .18, P   = .02), LTPA and loneliness ( r  = –.15, P   = .045), and loneliness and life satisfaction ( r  = –.69, P   < .001). Mediation analyses suggest that loneliness significantly mediated the relationship between LTPA and life satisfaction (indirect effect = .003, 95% bootstrap CI = .0004 to .0062, CSI = .113). Conclusion: This was the first study to show evidence of a negative association between LTPA and loneliness among people with SCI/D, and to establish a conceptual model for understanding the potential mediating role of loneliness in the relationship between LTPA and life satisfaction among people with SCI/D.